2008
DOI: 10.1073/pnas.0801102105
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-repressed mRNAs contain 40S but not 60S components

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that may target more than one-third of human genes, yet the mechanisms used by miRNAs to repress translation of target mRNAs are obscure. Using a recently described cell-free assay of miRNA function, we observe that miRNA-targeted mRNAs are enriched for 40S but not 60S ribosome components. Additionally, toeprinting analysis of miRNA-targeted mRNAs demonstrates that Ϸ18 nt 3 relative to the initiating AUG are protected, consistent with 40S ribosome subunits positioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 27 publications
3
88
0
2
Order By: Relevance
“…For example, miRNAs have been suggested to promote translation termination, interfere with the growing peptide, or block elongation (Olsen and Ambros 1999;Seggerson et al 2002;Maroney et al 2006;Nottrott et al 2006 ;Petersen et al 2006;Lytle et al 2007). Other experiments indicate that miRNAs block translation initiation, possibly by interfering with either 7-methyl-guanosine cap function or the joining of ribosomal subunits (Humphreys et al 2005;Pillai et al 2005;Chendrimada et al 2007;Kiriakidou et al 2007;Mathonnet et al 2007;Thermann and Hentze 2007;Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miRNAs have been suggested to promote translation termination, interfere with the growing peptide, or block elongation (Olsen and Ambros 1999;Seggerson et al 2002;Maroney et al 2006;Nottrott et al 2006 ;Petersen et al 2006;Lytle et al 2007). Other experiments indicate that miRNAs block translation initiation, possibly by interfering with either 7-methyl-guanosine cap function or the joining of ribosomal subunits (Humphreys et al 2005;Pillai et al 2005;Chendrimada et al 2007;Kiriakidou et al 2007;Mathonnet et al 2007;Thermann and Hentze 2007;Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the canonical model of RISC loading, Agos can form active RISC using single-stranded RNAs or DNAs ranging from 9-36 nucleotides (nt) (Wang et al 2008b), precursor miRNAs (pre-miRNAs) (Tan et al 2009), and long unstructured single-stranded RNAs (Tan et al 2009), suggesting flexibility in length and structure of oligonucleotides that can bind to Agos. Additionally, we (Wang et al 2006(Wang et al , 2007(Wang et al , 2008a(Wang et al , 2009a and others (Ricci et al 2011) have functionally shown that preannealed miRNA-mRNA duplexes can bind Agos and are translationally repressed in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Three models describing this theory are (i) prevention of ribosome recruitment, (ii) disruption of circularisation causing an open loop structure and (iii) formation of an inhibitory closedloop complex through competition with translation initiation factors for the mRNA m 7 G-cap structure. Disruption of ribosome recruitment was demonstrated by Wang et al (37) whereby CXCR4 artifi cial miRNA were able to inhibit translation by preventing the recruitment of the 60S subunit, likely mediated by eukaryotic translation initiation factor 6 (eIF6) in rabbit reticulocyte lysate. Studies in D. melanogaster Schneider cells (S2) showed that depletion of eIF6 had no effect on miRNA-mediated translational repression, or miRNA-dependent degradation of luciferase reporter Addition of CXCR4 repressed both cap-dependent and IRES-driven luciferase translation.…”
Section: Pre-initiation Silencingmentioning
confidence: 99%
“…(D) Inhibition of ribosome subunit assembly. The presence of RISC prevents the assembly of the ribosomal subunits preventing translation initiation, potentially by inhibition of eIF6 (37,40) . (E) Formation of an inhibitory closed loop.…”
Section: Post-initiation Silencingmentioning
confidence: 99%